2022
DOI: 10.3390/ijms232112893
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Ovarian Cancer Sensitivity to Paclitaxel and Platinum-Based Drugs: A Review of In Vitro Findings

Abstract: Ovarian cancer is one of the most dangerous gynecologic cancers worldwide, showing a high fatality rate and recurrence due to diagnosis at an advanced stage of the disease and the occurrence of chemoresistance, which weakens the therapeutic effects of the chemotherapeutic treatments. In fact, although paclitaxel and platinum-based drugs (carboplatin or cisplatin) are widely used alone or in combination to treat ovarian cancer, the occurrence of chemoresistance significantly reduces the effects of these drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 108 publications
(132 reference statements)
0
23
1
Order By: Relevance
“…The precise molecular mechanisms that support the relationship between autophagy and mitochondrial donation via TNTs and/or EVs remain to be elucidated. Data confirmed that the treatment of cancer cells with metformin can affect the formation of TNTs (Tossetta, 2022). For instance, mesothelioma and ovarian cancer cells treated with metformin exhibited the reduction of TNT formation via the inhibition of mTOR (Desir et al, 2016; Lou et al, 2012).…”
Section: Autophagy and Tntsmentioning
confidence: 55%
“…The precise molecular mechanisms that support the relationship between autophagy and mitochondrial donation via TNTs and/or EVs remain to be elucidated. Data confirmed that the treatment of cancer cells with metformin can affect the formation of TNTs (Tossetta, 2022). For instance, mesothelioma and ovarian cancer cells treated with metformin exhibited the reduction of TNT formation via the inhibition of mTOR (Desir et al, 2016; Lou et al, 2012).…”
Section: Autophagy and Tntsmentioning
confidence: 55%
“…Presently, synthetic chemotherapeutics are widely involved in solid tumor therapy together with radiotherapy and surgical operations. For instance, platinum-based antitumor drugs (such as cisplatin, carboplatin, oxaliplatin, satraplatin, and nedaplatin) [ 1 , 2 , 3 , 4 , 5 , 6 ], lonidamine, doxorubicin, and methotrexate [ 7 ] are commonly used chemotherapeutics in treating solid tumors. Despite their therapeutic anticancer effects, clinicians and patients still suffer from treatment failure of chemotherapeutic agents (even the latest generations) due to their systemic toxicity and cancer cells’ resistance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because this disease is usually asymptomatic or has nonspecific symptoms, more than 75% of patients are diagnosed at an advanced stage [ 2 ]. Moreover, the occurrence of chemoresistance also weakens the therapeutic effects of chemotherapeutic treatments [ 3 ]. Thus, the 5-year survival rate of OC is below 45% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%